Development of a model of personnel management in the hotel industry - Segeda, Iryna; Obolentseva, Larysa; Aleksandrova, Svitlana (Technology audit and production reserves, 2021)
The object of this research is personnel management in the hotel industry. The paper considers theoretical and practical aspects of the features of phased personnel management in the hotel industry, taking into account the specifics of the industry. The importance of the attitude of each employee to their responsibilities and the company as a whole was emphasized, and it was established that the minimum number of employees can provide the highest quality of service. In any case, there is a need for effective personnel management, in the purposeful activities of the management of the organization to develop its own concept, strategy of personnel policy and management methods. The main purpose of personnel management is formed. There are three groups of methods for personnel management, which almost completely reveal the step-by-step process of personnel management in the hotel industry. The necessity of application of complex technologies for achievement of more effective result is considered. A number of measures of nine stages of personnel management are prescribed. Rational use of service personnel is a prerequisite that ensures the continuity and proper quality of the service process, and, as a consequence, the successful implementation of the production program of the hotel industry. The study of the main indicators of labor should begin with an assessment of the dynamics of the number of personnel of the enterprise, the intensity of its movement and structure over a period of three to five years. Based on the study, a model of personnel management in the hotel industry, which determines the object and subject of management, their impact on each other, takes into account the stages of employee management. It will increase productivity, performance, organize work, monitor performance tasks, teamwork.